Genomic landscape of lung adenocarcinomas in different races - Shi, Huashan; Seegobin, Karan; Heng, Fei; Zhou, Kexun; Chen, Ruqin; Qin, Hong; Manochakian, Rami; Zhao, Yujie; Lou, Yanyan (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma is a molecularly heterogeneous disease. Several studies, including The Cancer Genome Atlas Research Network (TCGA) and Lung Cancer Mutation Consortium (LCMC), explored the genetic alterations among different ethnic groups. However, minority groups like Blacks are often under-represented in these relevant studies and the genomic alterations among racial groups are not fully understood. Methods: We analyze genomic characteristics among racial groups to understand the diversities and their impact on clinical outcomes. Results: Native Americans had significantly higher rates of insertions and deletions than other races (P<0.001). EGFR and KRAS were the highest discrepancy genes in the different racial groups (P<0.001). The EGFR exon 21 L858R point mutation was three times higher in Asians than in all other races (P<0.001). Asians, Whites, and Blacks had 4.7%, 3.1%, and 1.8 % ALK rearrangement, respectively (P<0.001). White patients had the highest rates of reported KRAS G12C (15.51%) than other races (P<0.001). Whites (17.2 %), Blacks (15.1 %), and Other (15.7 %) had higher rates of STK11 mutation than Asians (3.94%) (P<0.001). RET rearrangement and ERBB2 amplification were more common in Asian patients than in Other racial groups. Apart from point mutations, structural variations, and fusion genes, we identified a significant amount of copy number alterations in each race. Conclusions: The tumor genomic landscape is significantly distinct in different races. This data would shed light on the understanding of molecular alterations and their impacts on clinical management in different lung cancer patients.